(3cJGH cTa GdRjH aj GdYed HGdLjHs - (3eMeO Hf CMeO Hf YHO GdQMje GdeRj GdeGdcj , TeS GdOjf,J (B750 (3g` s ((3CMeO Hf GHQGgje GdSWMi s)
(3ChdgG (B:s
(3bGd GdTjN GdeRi GdeGdci hHYO abO hVYJ gPg GdQSGdI ai GdYed HGdLjH GdHGH GdChd ai LjH GdbhS hLjH JeGegG s
(3BNQgG (B:s
(3hEf TFJ fbdJ GdNjW Ydi JeGe GdEQJaGY GdPi gh ajg hONdJ ef GdehRi Edi GdSJjfi JLOQ GdLOQ hgh YTQhf LRAkG hdjcf Pdc BNQ GdQSGdI JeJ HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG s
Keywords: (3Gdadcs